Successes and Challenges of Optimal Trauma Care for Rural Family Physicians in Kansas - Berg, Gina M.; Dobson, Cheryl; Lee, Felecia A.; Hervey, Ashley M.; Kellerman, Rick (Kansas Journal of Medicine, 2019)
Introduction. Kansas has a regionalized trauma system with formal mechanisms for review, however, increased communication with rural providers can uncover opportunities for system process improvement. Therefore, this qualitative study explored perceptions of family medicine physicians staffing emergency departments (ED) in rural areas, specifically to determine what is going well and what areas needed improvement in relation to the trauma system. Methods. A focus group included Kansas rural family physicians recruited from a local symposium for family medicine physicians. Demographic information was collected via survey prior to the focus group session, which was audiotaped. Research team members read the transcription, identified themes, and grouped the findings into categories for analysis. Results. Seven rural family medicine physicians participated in the focus group. The majority were male (71%) with the mean age 46.71 years. All saw patients in the ED and had treated injuries due to agriculture, falls, and motor vehicle collisions. Participants identified successes in the adoption and enforcement of standardized processes, specifically through level IV trauma center certification and staff requirements for Advanced Trauma Life Support training. Communication breakdown during patient discharge and skill maintenance were the most prevalent challenges. Conclusions. Even with an established regionalized trauma system in the state of Kansas, there continues to be opportunities for improvement. The challenges acknowledged by focus group participants may not be identified through patient case reviews (if conducted), therefore tertiary centers should conduct system reviews with referring hospitals regularly to improve systemic concerns. KS J Med 2017;10(1):12-16.